SISTEM INFORMASI MONITORING PENDETEKSIAN DINI PENYAKIT COVID-19 BERDASARKAN GEJALA - Nadia Imawangi (2021)
Based on the results of monitoring through the covid19.go.id information channel managed by the Covid-19 Handling Task Force regarding the analysis of Covid-19 virus data as of July 18, 2021, there were 2,877,476 cumulative Covid- 19 cases in Indonesia, of which 542.236 (18.8%) Among them were active cases, 2,261,658 (78.6%) were declared cured from being confirmed, and 73,582 (2.6%) died and were confirmed to have contracted Covid-19. In another previous report, as of March 31, 2020, there were 1,528 confirmed cases, with 136 deaths, causing the Covid-19 mortality rate in Indonesia to be 8.9%, which is the highest number in Southeast Asia. This becomes frightening for Indonesian citizens, especially for those who cannot do their work at home. Therefore, there is a need for early detection for the community to find out the level of risk of being exposed to Covid-19 quickly. One of them is building an Information System for Monitoring the Early Detection of Covid-19 Disease based on Symptoms. The detection uses the Forward Chaining Method, with several rules that have been previously made by related research. The design of mobile-based applications for users and web for admins uses the Agile Software Development development method so that they can adapt to all changing application needs. This system will be an Android application built using Apache Cordova with the Laravel framework.